Model of Activities of the Resource Training Center of the Russian State Social University in Terms of Professional Orientation and Employment of Persons with Disabilities - Bikbulatova A.A; Karplyuk A.V; Tarasenko O.V (Moscow State University of Psychology and Education, 2017)
The paper focuses on the importance of professional and vocational guidance for persons with disabilities. It describes the main approaches to providing such type of guidance to the disabled students and reveals the technologies of motivating people with disabilities to seek education and to make informed choices of profession. The research was aimed at developing the model of career guidance offered at resource and training centers established by the Ministry of Education and Science of the Russian Federation on the basis higher educational institutions. The paper presents the developed model of professional and vocational guidance for persons with disabilities and explains the algorithm of its implementation in the resource and training centers. Also, the paper gives recommendations on how to change the technology of communication between universities, regional job centers and offices of medical and social assessment.